Estimating the moisture regime in variably saturated arsenic contaminated alluvial sediments by using hydrus-1d with daily meteorological data - Dimitar ANTONOV; Tsvetan KOTSEV; Aleksey BENDEREV; Nathalie VAN MEIR; Petar GERGINOV; Velimira STOYANOVA; Emilia TCHERKEZOVA (European Journal of Geography)
As a result of historical mining activities, some layers in the Ogosta Valley`s floodplain sediments are highly enriched in arsenic (As). Reductive release of iron (Fe) and As in the floodplain soil could be expected under reducing conditions, which would lead to an increase of the more toxic As species in the soil pore water. Therefore, it is important to understand whether the vadose zone in the Ogosta’s floodplain is a subject to water saturation during intensive rainfalls. The study provides a model based on the HYDRUS-1D code, along with the mathematical description of processes implemented into, especially those used to estimate the daily evapotranspiration rates and water flow from the soil surface to the groundwater level during ten-days scenarios including intensive rainfalls. The results from the simulations for April and July are compared in order to reveal the moisture regime of the vadose zone in the river floodplain of the Ogosta Valley